2013
DOI: 10.1371/journal.pone.0076040
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A and IL-2-Expanded Regulatory T Cells Cooperate to Inhibit Th1-Mediated Rejection of MHC II Disparate Skin Grafts

Abstract: Several evidences suggest that regulatory T cells (Treg) promote Th17 differentiation. Based on this hypothesis, we tested the effect of IL-17A neutralization in a model of skin transplantation in which long-term graft survival depends on a strong in vivo Treg expansion induced by transient exogenous IL-2 administration. As expected, IL-2 supplementation prevented rejection of MHC class II disparate skin allografts but, surprisingly, not in IL-17A-deficient recipients. We attested that IL-17A was not required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
(33 reference statements)
0
6
1
Order By: Relevance
“…We found that both PA and OA promoted a reduction in the percentage of these cells in both concentrations when compared to control cells. Treg lymphocytes reduce the clonal expansion of Th1 and Th17A cells and, consequently, decreasing the inflammatory response [30, 31]. However, in the present study, PA inhibited proliferative capacity of lymphocytes and the production of inflammatory cytokines (Th1 and Th17 response), as well as the percentage of Treg cells.…”
Section: Discussioncontrasting
confidence: 53%
“…We found that both PA and OA promoted a reduction in the percentage of these cells in both concentrations when compared to control cells. Treg lymphocytes reduce the clonal expansion of Th1 and Th17A cells and, consequently, decreasing the inflammatory response [30, 31]. However, in the present study, PA inhibited proliferative capacity of lymphocytes and the production of inflammatory cytokines (Th1 and Th17 response), as well as the percentage of Treg cells.…”
Section: Discussioncontrasting
confidence: 53%
“…For production of ovalbumin peptide (pOVA)-conjugated 8D1, we used 8D1 mAb 15 , 33 (grown from hybridoma), chemical linker N -succinimidyl-6-maleimido-caproate (EMCS, Sigma Aldrich), and a custom OVA 323–339 peptide containing an amino terminal cysteine residue and C-terminal biotin tag (Mimotopes, Notting Hill, VIC, Australia). As control for these experiments, isotype control mouse IgG1 (clone MOPC-21, Bio X Cell) 58 was used. For activation and polarization of OT-II T cells, cells were cultured in RPMI 1640 supplemented with 10% heat-inactivated fetal calf serum (both from Life Technologies), 2-mercaptoethanol, recombinant mouse (rm)IL-12 (eBioscience), rat anti-IL-4 (clone 11B11, ATCC) and rmIL-2 (R&D Systems).…”
Section: Methodsmentioning
confidence: 99%
“…IL-2/JES6-1 complexes are also stimulatory for ILC2 that express trimeric IL-2Rs, which contributes to IL-5 production and eosinophilia [30,57]. IL-2/JES6-1 complexes have shown promising results in the prevention of pancreatic [56] and skin [58] allograft rejection as well as in the treatment of several autoimmune and inflammatory diseases in mice, including type 1 diabetes in nonobese diabetic mice [59], experimental autoimmune encephalomyelitis (a model of multiple sclerosis) [56], experimental myasthenia [60], collagen-induced arthritis [61], dextran sodium sulfate-induced acute colitis [13], and T cell-mediated allergic airway disease [62]. Interestingly, administration of IL-2/JES6-1 complexes also improved the pathology of some metabolic, cardiovascular, and degenerative disorders, such as murine obesity-induced inflammation and insulin resistance ('type 2 diabetes') [63], atherosclerosis in high-fat diet-fed apolipoprotein E-deficient animals [64], and the mdx mouse model of Duchenne muscular dystrophy [65], that feature inflammatory infiltrates and are thus amenable to suppression by CD25 + Foxp3 + Treg cells.…”
Section: Il-2/mab Complexesmentioning
confidence: 99%